Implications of AfCFTA Tariff Reductions for EAC Exports to Africa - Evious Zgovu; Oliver Morrissey (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2024)
This paper provides estimates of the potential for EAC member countries to increase exports to the rest of Africa under AfCFTA, assuming the other countries reduce tariffs on imports from the EAC. We adopt a simple approach to identify the markets (countries) and products most likely to benefit and consider only growth of existing imports from the EAC; the assumption is that EAC have evident export capacity in such products and markets, and that these products are unlikely to be excluded from liberalisation by African importing countries. Results suggest that the EAC could expand exports overall by 10-15%, largely concentrated in relatively close countries and agriculture and resource-based products. Relatively distant markets in North and West Africa do offer potential to EAC countries except Rwanda (concentrated on DRC) and Tanzania (concentrated on Southern Africa). These estimates are complemented with analysis of the welfare effects on Kenya, Tanzania and Uganda of eliminating tariffs on imports from the rest of Africa - overall imports increase by around 10% and, as these tend not to displace intra-EAC trade, the consumption gains from lower prices deliver a positive welfare effect (negligible relative to GDP). The EAC can anticipate moderate gains from AfCFTA and, by identifying the markets and products most likely to be affected, the study provides a guide to policymakers in EAC countries on sectors to target in supporting export growth within Africa.
Keywords: F10; F14; F15; O55; 330; East African Community (EAC); African Free Trade (AfCFTA); Tariff Reductions; intra-African exports